Laparoscopic cholecystectomy in a patient with situs inversus totalis: a case report - Bogarapu, Chaithanya Babu; Savalam, Rathna Kishore Bujjitha; Chinthagada, Jayaraj; Kattupalli, Satish Chaitanya (International Journal of Research in Medical Sciences, 2017)
Situs inversus totalis is a rare congenital condition present in approximately 0.01% of the population in which the major visceral organs are reversed from their normal position and can pose difficulties in the diagnosis and management of acute abdominal pathology. Symptomatic cholelithiasis is very common in India and laparoscopic cholecystectomy is the gold standard treatment at present. Laparoscopic surgery in a situation of situs inversus is challenging due to the mirror-image anatomy. Diagnostic pitfalls and technical details of the laparoscopic cholecystectomy are discussed.